The effect of isotretinoin on the development of depression in patients after anti-acne treatment - Paprocki, Michał; Mataczyńska, Anna; Paprocki, Jakub; Nowakowska, Maria; Arciszewska, Klaudia; Dobosz, Mateusz; Pieniążek, Jakub Maciej; Padkowska, Aleksandra; Szpernalowska, Anna; Buczkowski, Jakub (Quality in Sport, 2024)
This paper reviews the existing scientific literature on the relationship between isotretinoin, a vitamin A derivative used to treat severe acne, and the development of depression in patients undergoing treatment. Isotretinoin is highly effective for cases of treatment-resistant acne due to its anti-inflammatory, antibacterial properties, and ability to regulate sebum secretion and keratinization. However, its use is also associated with numerous adverse effects, particularly psychiatric disorders, including depression. The connection between isotretinoin use and the onset of depressive symptoms remains controversial, with studies providing conflicting evidence. This review aims to critically examine the current research to clarify the potential risks of depression associated with isotretinoin.